2016
DOI: 10.1097/qad.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Novel relationships of markers of monocyte activation and endothelial dysfunction with pulmonary dysfunction in HIV-infected persons

Abstract: Objective Chronic obstructive pulmonary disease (COPD) is a common co-morbidity in HIV, with prevalence and severity of disease incompletely explained by risk factors such as smoking and age. Unique HIV-associated factors, including microbial translocation, monocyte activation, and endothelial dysfunction, have been described in other co-morbidities, but have not been investigated in relation to pulmonary abnormalities in HIV. This study assessed the relationship of these pathologic processes to pulmonary func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 99 publications
4
71
3
Order By: Relevance
“…Spirometric results were normal on average with a median (IQR) postbronchodilator FEV 1 % predicted of 98 (88-109); however, diffusing capacity was low on average with a median (IQR) DL CO % predicted of 69 (57-81). The median (IQR) percentage of voxels , -910 HU was 7 (3-16), WA% was 46 (42-49), tricuspid regurgitation velocity was 2.4 (2.2-2.6), and estimated pulmonary artery systolic pressure was 33 (29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…Spirometric results were normal on average with a median (IQR) postbronchodilator FEV 1 % predicted of 98 (88-109); however, diffusing capacity was low on average with a median (IQR) DL CO % predicted of 69 (57-81). The median (IQR) percentage of voxels , -910 HU was 7 (3-16), WA% was 46 (42-49), tricuspid regurgitation velocity was 2.4 (2.2-2.6), and estimated pulmonary artery systolic pressure was 33 (29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…whipplei . However, we chose these inflammatory markers because studies have shown that plasma levels of these cytokines are negatively associated with lung function in HIV-infected individuals [ 16 , 17 ]. In this cohort, 93.4% participants received ART, median CD4 + cell count was more than 600 cells/μl, and median plasma HIV viral load was about 100 copies per ml.…”
Section: Discussionmentioning
confidence: 99%
“…PLWH are more susceptible to mycobacterial infection, particularly in TB-endemic regions such as SSA[12]. Tuberculosis increases the risk of COPD through several mechanisms, including infection-related parenchymal scarring and chronic airways inflammation from latently-infected pulmonary macrophages[2527]. HIV itself may also directly cause COPD through the consequences of HIV-infected pulmonary macrophages, which lead to alveolar inflammation, epithelial barrier dysfunction, altered pulmonary oxidant-antioxidant balance, increased cellular apoptosis and altered respiratory tract microbial colonization, all of which are implicated in COPD pathogenesis[2831].…”
Section: Discussionmentioning
confidence: 99%
“…HIV itself may also directly cause COPD through the consequences of HIV-infected pulmonary macrophages, which lead to alveolar inflammation, epithelial barrier dysfunction, altered pulmonary oxidant-antioxidant balance, increased cellular apoptosis and altered respiratory tract microbial colonization, all of which are implicated in COPD pathogenesis[2831]. Indeed, HIV-associated systemic biomarkers of inflammation and immune activation, which persist despite viral suppression, have been associated with pulmonary dysfunction[26,27]. Associations between tuberculosis and COPD among PLWH in North American cohorts have not been described, possibly related to lower tuberculosis prevalence.…”
Section: Discussionmentioning
confidence: 99%